The effect of the training program on the quality of life in patients with asthma based on the Precede model in Ahvaz, Iran - Nejad, Mina Motaghi; Nejad, Ghodratollah Shakeri; Tavakol, Heshmatollah; Cheraghi, Maria (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Aim: The aim of the study was to determine the effect of the training program based on the Precede model and its main components on improving the quality of life in patients with asthma. Material and methods: It was a randomized quasi-experimental study done on 120 patients with asthma who were referred to the Imam Khomeini hospital in Ahvaz who were selected using the convenience sampling method and were randomly divided into intervention and control groups. The data collection tool consisted of two questionnaires. The first questionnaire evaluated the quality of life in patients with asthma and the other one was developed by the researcher based on the structures of the Precede model. Training intervention was conducted during four sessions twice a week and each session was carried out for an hour based on the structures of the Precede model. In order to achieve the results, SPSS software, even t-test, and 2 were used. Results: The results showed that after the training intervention in the experimental group, the mean scores of predisposing factors (p < 0.001), enabling factors, reinforcing factors and behavioral factors were significantly increased (p < 0.001) as compared to the control group. A significant difference was observed in the mean scores of quality of life in two groups after the intervention (p < 0.001), and the quality of life of patients in the experimental group was improved after the training intervention. Conclusions : The design and implementation of the training program based on the Precede model can have a positive effect on the improvement of quality of life in patients with asthma.